Gaceta Técnica magazine. A new look (Gaceta Técnica, 2018)
The journal Gaceta Técnica in this new issue of the year 2018 opens on the Open Journal Systems platform, as part of an institutional project led by the Institutional Commission of Scientific Journal Directors of the Centroccidental Lisandro Alvarado University. The objective, in the first instance, is to place the journals attached to the institution in a free management platform, for free access to the contents published therein, favoring editorial management, visibility and harvesting of articles by of the various indices. The journal Gaceta Técnica in this way acquires a new look, in the search to maintain the knowledge that is projected through it.